Boron/sodium co-doping enhances phase transformation in TiO2 nanofibers and amplifies photoelectrochemical nucleic acid oxidation detection - Aykut, Yakup; Koc, Umit (Elsevier, 2026)
Background: Oxidative damage in genetic molecules disrupts cellular function and poses long-term risks to organismal health, underscoring the need for early, rapid, and sensitive detection methods. Early and precise detection of this oxidative damage in genetic molecules can enable necessary precautions to be taken and initiate the treatment process early, thereby saving the lives of patients. Oxidation detection and analysis using electrochemical methods are frequently employed. The properties of the electrodes used in electrochemical measurements are significant for sensor sensitivity. Recent studies have shown that sensor sensitivity can be tremendously enhanced by using nanomaterials in electrodes. Results: In this study, boron/sodium B/Na co-doped TiO2 nanofibers were fabricated via a sol-gel electrospinning process and employed for photoelectrochemical (PEC) detection of guanine oxidation in the genetic molecules. Compared with pristine TiO2 nanofibers, B/Na doped structures exhibited significantly enhanced oxidation signals under dark, solar, and ultraviolet irradiation. Systematic investigations revealed that increasing the dopant content promoted a controlled anatase to rutile phase transformation, while excessive doping disrupted the TiO2 crystalline framework. Higher calcination temperatures were also found to facilitate appropriate phase transformation. Importantly, nanofibers containing a mixed anatase-rutile composition provided the highest sensitivity for guanine oxidation detection. Significance: Using a facile one-step sol-gel electrospinning method, we demonstrated that B/Na co-doping can precisely tune the anatase-to-rutile transformation by adjusting dopant content and calcination conditions. This structural modulation significantly enhanced the PEC detection of guanine oxidation. These findings demonstrate a direct correlation between structural modulation and biosensing performance. The presented approach establishes a scalable pathway to design multifunctional oxide nanofibers for early-stage genetic oxidation diagnostics, offering new opportunities for next-generation biomedical monitoring and precision healthcare.
Keywords: Guanine Oxidation; Ceramic Nanofibers; Sol-Gel Electrospinning; Photoelectrochemical Detection; Phase Transformation